2005
DOI: 10.1002/cncr.21148
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian carcinoma screening in women at intermediate risk

Abstract: Objective: To analyze the frequency of the haplotypes of β‐globin gene cluster in randomly selected patients withsickle cell disease (SCD), attended in the Children's Hospital of Panama. Methods: Five polymorphic sites in the β‐globin gene cluster were analyzed by polymerase chain reaction (PCR) followed by restriction digestion and agarose gel electrophoresis in a total of 100 patients, including 95 homozygous for HbS (sickle cell anemia) and 5 compound heterozygotes for HbS and HbC genes (HbSC disease). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…This transient effect of an abnormal OCS result mirrors the findings of studies observing the psychological impact of familial breast screening [27,28] and the early studies of familial OCS which found no evidence of prolonged distress [13]. In contrast, Kauff et al [14] found reduced quality of life six months after receiving an abnormal result, which may reflect the high rate of false positive results and endometrial sampling observed in their study.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…This transient effect of an abnormal OCS result mirrors the findings of studies observing the psychological impact of familial breast screening [27,28] and the early studies of familial OCS which found no evidence of prolonged distress [13]. In contrast, Kauff et al [14] found reduced quality of life six months after receiving an abnormal result, which may reflect the high rate of false positive results and endometrial sampling observed in their study.…”
Section: Discussionsupporting
confidence: 49%
“…Total subscale scores yield cut-off values for mild (scores from 8 to 10), moderate (11)(12)(13)(14)(15) or severe (>16) depression or anxiety. The HADS showed strong reliability and validity in women at increased risk of breast cancer [26].…”
Section: General Anxiety and Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…also published on the impact of ovarian cancer screening on QOL. In this study of 135 patients, abnormal ovarian cancer screening results were associated with a significant decrease in the Mental Component Summary form of the SF-36 [6]. Finally, the Gynecologic Oncology Group (GOG) also published initial data regarding RRSO and CA-125 in women at risk for ovarian cancer (GOG 199) [7].…”
Section: Screening/early Diagnosismentioning
confidence: 99%
“…Furthermore, OCS is associated with frequent false-positive screening test results and anxiety [17, 18]. More recently, the Risk of Ovarian Cancer Algorithm (ROCA), a novel screening strategy consisting of longitudinal CA-125 measurements analyzed by Bayesian modeling, followed by secondary screening with TVUS if indicated, has shown promise among average-risk [19], and high-risk women [20], with no clinically significant psychological morbidity among average-risk women undergoing repeat testing following abnormal screening tests [21].…”
Section: Introductionmentioning
confidence: 99%